Moleculer analysis of genotype kappa casein and composition of goat milk Etawah grade, Saanen and their crossbred - Yayu Zurriyati; R.R. Noor; R.R.A. Maheswari (Jurnal Ilmu Ternak dan Veteriner, 2011)
Polymorphism of goat casein gene closely linked to the quality of milk protein. κ-casein is one of the casein fractions that influence the shape and stability of grain milk. This study is aimed to identify the variation of genotype κ-casein and related with milk quality from Etawah grade, Saanen and their crossbreed (PE-SA). The number of dairy goats used in this study was 150 animals consisted of Etawah grade (48 animals), Saanen (51 animals) and PE-SA (51 animals). Steps of experiment were: blood and milk sampling collection, DNA amplification by PCR and the product digestion using Pst1 enzyme, κ-casein gene sequencing and analyzing the quality of fresh milk. The results showed that κ-casein gene is monomorphic by PCR-RFLP (Pst1) for all the goat breeds, but DNA sequencing indicated 38 point of mutation.  Observation on goat milk quality showed that Etawah grade milk had highest (P < 0.05) density value (1.033 ± 0.002) and solid non fat (9.577 ± 0.704%) than those of Saanen and PE-SA fresh milk goat. Key Words: Dairy Goats, Κ-Casein Gene, PCR-RFLP, Milk